2003
DOI: 10.1002/bit.10680
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐assembly of functionalized particulate monolayer on C18‐derivatized SiO2 surfaces

Abstract: This work describes a simple approach to immobilize functionalized colloidal microstructures onto a C 18 -coated SiO 2 substrate via specific or non-specific biomediated interactions. Biotinylated bovine serum albumin pre-adsorbed onto a C 18 surface was used to mediate the surface assembly of streptavidin-coated microbeads (2.8 µm), while a bare C 18 surface was used to immobilize anti-Listeria antibody-coated microbeads (2.8 µm) through hydrophobic interactions. For a C 18 surface pre-adsorbed with bovine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…beadsrmL for 2 min and air dried to give the fiber of Figure 3b. Rationale and experimental protocols for micropattern-Ž ing beads on oxide surfaces is described elsewhere Huang et . al., 2003 .…”
mentioning
confidence: 99%
“…beadsrmL for 2 min and air dried to give the fiber of Figure 3b. Rationale and experimental protocols for micropattern-Ž ing beads on oxide surfaces is described elsewhere Huang et . al., 2003 .…”
mentioning
confidence: 99%
“…(Peterson, 2005) For instance, functionalized microparticles may be fixed onto surfaces using hydrophobic/hydrophilic interactions or assemblies of oligonucleotides.(T.T. Huang et al, 2003;McNally et al, 2003) A number of different methods have been reported for trapping particles into a microdevice, some using physical barriers to retain beads, others using magnetic fields to manipulate and trap beads. (Linder et al, 2002;J.-W. Choi et al, 2001) An interesting entrapment method is reported in the previous section by Malmstadt et al (Malmstadt et al, 2003(Malmstadt et al, , 2004 As reported by Andersson et al, a series of pillars could constrain beads placed in a microfluidic chip and this approach was useful in fabricating devices for single-nucleotide polymorphism analysis and capillary electrochromatography.…”
Section: Immobilization Methodsmentioning
confidence: 99%
“…The microbead loading efficiency can be enhanced by centrifugation, or by applying electric charges or magnetic fields (Manesse et al 2013). Other techniques such as the use of affinity binding between biotin and streptavidin to functionalize the matrix and the beads to immobilize the beads (Huang et al 2003). Surface modifications based on the composition of beads and matrix, in order to attach microbeads have been described in a patent by Margel (Margel 1997).…”
Section: Multiplexing Technologiesmentioning
confidence: 99%